In situ soil washing on metal-contaminated sandy soil by sedimentation method a new approach on soil remediation - Budianta, Wawan; Salim, Chris; Hinode, Hirofumi; Ohta, Hideki
We propose a new approach of in situ soil remediation called in situ soil washing by sedimentation method, by injecting high air pressure into mixing water sandy soil ground and hydraulically separate soil particles based on their particle size and density. This physical separation exploits the distribution of contaminant in soil by physically separating a select, contaminant rich fraction. The advantage of this method is on the washing and separation processes that are carried out simultaneously during remediation process. The suitability of the method for heavy metal remediation was examined by batch sedimentation column experiment. Laboratory experiment was effective to produce a distinct size separation of the soil into coarse, fine and wash water and indicate significant reduction in heavy metal level (90 percent). The coarse fraction had the least level of heavy metal contaminant while the fine fraction contained the highest heavy metal concentration and a very small amount of the original contaminant was retained in the coarse fraction. The experimental results show that the removal efficiencies depend on the initial concentration of metal in the soil sample, the duration of washing and the addition of biosurfactant in the washing solution.
Keywords: In situ soil washing; Heavy metal contamination; Sedimentation method; Removal efficiencies